2018
DOI: 10.15560/14.4.637
|View full text |Cite
|
Sign up to set email alerts
|

The millipedes and centipedes of Chiapas amber

Abstract: An inventory of fossil millipedes (class Diplopoda) and centipedes (class Chilopoda) from Miocene Chiapas amber, Mexico, is presented, with the inclusion of new records. For Diplopoda, 34 members are enumerated, for which 31 are described as new fossil records of the orders Siphonophorida Newport, 1844, Spirobolida Bollman, 1893, Polydesmida Leach, 1895, Stemmiulida Pocock, 1894, and the superorder Juliformia Attems, 1926. For Chilopoda 8 fossils are listed, for which 3 are new records of the order Geophilomor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Simojovel, Totolapa, and Estrella de Belén are considered the type localities of a Conservation Lagerstätte with a remarkable abundance of amber inclusions, predominantly terrestrial arthropods and plants (Riquelme et al, 2013(Riquelme et al, , 2014b. Here the sedimentary record is strongly associated with a lowland-fluvial environment close to the coastal plain (Graham, 1999;Langenheim, 2003;Perriliat, Vega & Coutiño, 2010;Riquelme et al, 2013); and paleobiota resembles those found in current humid tropics (Riquelme & Hernández-Patricio, 2018). Chiapas amber has chemical signatures that match with the extant resins of the genus Hymenaea (sensu Langenheim, 1966), which are also currently distributed in the tropics (Langenheim, 2003;Riquelme et al, 2014b)…”
Section: Geological Settingmentioning
confidence: 96%
See 2 more Smart Citations
“…Simojovel, Totolapa, and Estrella de Belén are considered the type localities of a Conservation Lagerstätte with a remarkable abundance of amber inclusions, predominantly terrestrial arthropods and plants (Riquelme et al, 2013(Riquelme et al, , 2014b. Here the sedimentary record is strongly associated with a lowland-fluvial environment close to the coastal plain (Graham, 1999;Langenheim, 2003;Perriliat, Vega & Coutiño, 2010;Riquelme et al, 2013); and paleobiota resembles those found in current humid tropics (Riquelme & Hernández-Patricio, 2018). Chiapas amber has chemical signatures that match with the extant resins of the genus Hymenaea (sensu Langenheim, 1966), which are also currently distributed in the tropics (Langenheim, 2003;Riquelme et al, 2014b)…”
Section: Geological Settingmentioning
confidence: 96%
“…The polydesmid millipedes of the family Pyrgodesmidae currently show a Pantropical distribution (Enghoff et al, 2015). However, the fossil record is limited to amber inclusions from Miocene deposits of the Dominican Republic and Mexico (Shear, 1981;Santiago-Blay & Poinar, 1992;Riquelme & Hernández-Patricio, 2018). Fossil specimens of Dominican amber have been assigned to the genera Docodesmus Cook, 1896a, Iomus Cook, 1911, Lophodesmus Pocock, 1894and Psochodesmus Cook, 1896b(Shear, 1981Santiago-Blay & Poinar, 1992), and the only fossil specimen described at the species level that is known so far is Docodesmus brodzinskyi Shear, 1981.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cretaceous amber inclusions come from different strata, including the most emblematic amber sites, such as Lebanon (Nguyen Duy-Jacquemin & Azar, 2004), France (Nguyen Duy-Jacquemin & Azar, 2004), and Myanmar (Rasnitsyn & Ross, 2000; Grimaldi et al ., 2002; Ross & Sheridan, 2013; Liu et al ., 2017; Zhang, 2017; Ross, 2018; Wesener & Moritz, 2018; Jiang et al ., 2019; Moritz & Wesener, 2019, 2021; Stoev et al ., 2019; Su et al ., 2019, 2020). In the Cenozoic, most fossil materials are also preserved as amber inclusions from exceptional conservation sites, such as those in the Baltic region (Koch & Berendt, 1854; Menge, 1854; Hoffman, 1969; Wesener, 2019), India (Srivastava et al ., 2006), Dominican Republic (Shear, 1981; Santiago-Blay & Poinar, 1992), and Mexico (Riquelme et al ., 2013; 2014; 2021; Riquelme & Hernández-Patricio, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Wesener & Moritz (2018) published an inventory of the Myriapoda, including Diplopoda, from the lowermost Upper Cretaceous amber of Myanmar. Riquelme & Hernández-Patricio (2018) published the first inventory of Diplopoda from the Lower Miocene Chiapas amber. They initially listed 34 records in four orders, six families, five genera, and three species.…”
Section: Introductionmentioning
confidence: 99%

Diplopoda in the world fossil record

Álvarez Rodríguez,
Riquelme,
Patricio
et al. 2024
Preprint
Self Cite